IJCM_148A: Difference in unmet supportive care needs of patients and informal caregivers with advanced cancer, between developed and developing countries: A scoping review - Malar Madhu P; Jain Animesh; Holla Ramesh; Rao Rajath; Rao Mithun; Jose Jobinse (Wolters Kluwer Medknow Publications, 2024)
Background: Cancer's global impact is surging, burdening both developed and developing nations. Therapeutic advances extend life but heighten morbidity, highlighting unmet needs. This review aims to investigate differing unmet supportive care needs for advanced cancer patients and caregivers between developing and developed countries. Objectives: 1. To identify and summarize the existing literature on unmet supportive care needs in patients and their informal caregivers, under groups of developed and developing countries 2. To examine the differences between the needs of the two groups Methodology: The review includes quantitative studies assessing the unmet supportive care needs of adult advanced cancer patients and their caregivers. Excluded are clinical-focused, pilot/protocol works, non-English content, and those not directly assessing needs. Exhaustive searches were conducted on PubMed and SCOPUS up to August 2023. Boolean search combining "advanced cancer" and "unmet supportive care needs" was executed. Results were screened on title, abstract, full text. Studies were grouped by country, and categorized as developed or developing based on HDI. Data was collected on standardized data extraction sheets. Results: Cancer patients and caregivers globally, irrespective of economic development, grapple with substantial unmet needs such as psychological distress, economic hardships, and limited access to comprehensive information. Developing countries, in particular, confront heightened financial difficulties, healthcare disparities between urban and rural areas, and a lack of tailored support for disease-specific requirements. Cultural nuances and regional disparities contribute to varied challenges, with a notable research gap in understanding the diverse struggles faced by individuals in developing countries. Conclusion: Recognizing and addressing the nuanced challenges faced by cancer patients and caregivers, particularly in developing countries, is crucial for fostering equitable and comprehensive cancer care. Bridging these gaps requires targeted interventions that account for cultural diversity, regional variations, and the unique needs of individuals navigating the complexities of cancer.